The Concept of Building a Sakinah Household in Long-distance Marriage in Bangkalan Madura: A Psychological Perspective Study - Jezeri, Jezeri; Royana, Laela; Afida, Herlina Nur (Faculty of Sharia and Islamic Law Institut Agama Islam Negeri Bone, 2023)
This study aims to describe long-distance marriage and its impact on family harmony. Researchers found a unique fact in the field, that there are several families who have similar backgrounds in undergoing long-distance marriages, but the success rate is different. There are couples who are harmonious and not secetious, there are couples who must end in divorce. Therefore, long-distance marriage needs to be studied in depth how the concept of long-distance marriage must be known and applied in the family. This study uses qualitative methods that examine the phenomenology of long-distance marriage using interview techniques with three informants in the city of Bangkalan, Madura. The results of this study can be concluded that long-distance marriage has four potentials, both positive and negative. The positive potential of long-distance marriage is that the economy is affordable and more energy efficient without the need to return to a distant home, motivated by enthusiasm for work and generosity. While the negative impacts are not met biological needs, the existence of multiple roles for husband or wife in the family, lack of affection for children and frequent infidelity. While efforts that can resolve or minimize the negative impact of long-distance marriage consist of six factors, namely marrying because of Allah SWT, loving each other, the openness of each partner, being wise and polite, strengthening communication and deliberation, patience and gratitude, forgiveness and tolerance.